2009
DOI: 10.1080/10599240902799798
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Farming Activities and Respiratory Health in Rural School Age Children

Abstract: This study assessed the prevalence of asthma in Canadian children living on and off farms and the risk of asthma and respiratory symptoms of children exposed to certain farming activities. A cross-sectional survey was sent to parents of school children ages 6 to 13 living in an agricultural community in rural Saskatchewan. History of asthma and respiratory symptoms (cough, phlegm, or wheeze), location of home, and exposure to farming activities including haying, harvesting, moving, or playing with hay bales, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In addition, there was decreased incidence of asthma and atopy in rural Canadian children raised on a farm, especially girls for current wheeze (OR 0.7) and asthma (OR 0.59) (Ernst and Cormier 2000). However, increased rate of respiratory symptoms were reported in children that cleaned large animal pens (Farthing et al 2009). …”
Section: Airway Disease Manifistationsmentioning
confidence: 99%
“…In addition, there was decreased incidence of asthma and atopy in rural Canadian children raised on a farm, especially girls for current wheeze (OR 0.7) and asthma (OR 0.59) (Ernst and Cormier 2000). However, increased rate of respiratory symptoms were reported in children that cleaned large animal pens (Farthing et al 2009). …”
Section: Airway Disease Manifistationsmentioning
confidence: 99%
“…Emptying grain bins regularly was associated with higher FEV 1 and FVC compared with those not regularly participating. Certain early farm exposures have been shown to have inverse associations with asthma presence including living on farm in the first year of life, drinking unpasteurized milk in the first year of life and mother living on farm while pregnant …”
Section: Discussionmentioning
confidence: 99%
“…Certain types of farming and farming activities have been shown to be protective against asthma including livestock farming and activities including livestock, riding horses and cleaning or playing in pens/corrals . Grain‐farming activities were associated with higher rates of asthma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher infant mortality rates and an increased risk of premature births were found in Pennsylvania, United States [13] . Farthing, et al (2009) found that children exposed to grain bins on farms in rural Saskatchewan, Canada, had more than two times the risk of developing asthma and respiratory issues than children who were not exposed [14] .…”
Section: Relative Riskmentioning
confidence: 99%